Interactive Learning for Lower-Secondary Student: C++ Language - SA'IMAN, AIZUDDIN (Universiti Teknologi PETRONAS, 2011)
Interactive learning is one of the methods to acquire knowledge and information through hands on. It is the opposite of passive learning which is merely a process of observing a learning process or listening to knowledge or information. My Final Year Project, "Interactive Learning for Lower-Secondary Student: C++ Language", aims to provide a revolutionary learning process of learning programming language, specifically C++ language, through a simple and interactive way. Throughout this report, I will discuss in details on my project. This report will first describe the motivation and objective of my project, and also introduced the concept of Interactive Learning.